The Essential Minerals for Rumen Metabolism - Muliani; Yasin, Suhbudy; Dilaga, Syamsul Hidayat; Jalaludin (Jurnal Biologi Tropis, 2024)
Minerals are a constituent element of nutrition with functions as body defense, reproduction, production and animal body health. In general, minerals act as catalysts that will balance cell membranes, balance acid bases, make enzymes active, and are involved in the fermentation process of rumen microbes. In ruminants, the important role of minerals is to influence the symbiotic micriflora in the digestive tract. The research instrument of this research is Scanning Electron Microscope (SEM) which is integrated with testing with the Energy Dispersive X-ray Spectroscopy (EDX) research instrument. Sampling of forage was carried out at the Teaching Farm Lingsar, Matataram University. Each forage sample was taken approximately 53 g fresh weight. The parameters used are the content of Zinc (Zn), Manganese (Mn), Copper (Cu), Cobalt (Co), and Selenium (Se). Data from the analysis of essential mineral content using SEM is statistically descriptive with data tabulation, data conversion, data averaging and processing with the help of Microsoft Excel. The results of several experiments using Scanning Electron Microscope (SEM) based on the elements of Zn, Mn, Cu, Co and Se, among others: The results of the percentage of Zn elements for grass 0.31% and legumes 0.65%. The results of the percentage of Mn elements for 0.31% and 0.65% legumes. The results of the percentage of Cu elements for grass 4.87% and legumes 7.15%. The results of the percentage of Co elements for grass 0.33% and legumes 0.21%. The results of the Se element percentage for grass 0.23% and legumes 0.7%.